Otomatisasi Sistem Keamanan Loker Menggunakan Deteksi Wajah Berbasis Iot Dengan Notifikasi Telegram - Ivang Pangestu; Petricia Oktavia (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Lockers are something that is provided to store valuable items. The use of lockers in this modern era is different from conventional lockers where lockers that use conventional locks are not well protected. At this time conventional keys are less practical because they can still be duplicated and lack of supervision. Sometimes users forget to put it or accidentally fall and then lost. This study uses face recognation with the esp32 cam microcontroller which gets data from the recordings of the esp camera to move the selenoid. This system is also equipped with an information system using Telegram. From the results of research conducted, if all components work well, the camera sensitivity value is 100% from 15 trials with rare faces to the camera 30cm but the level of detection accuracy decreases when the detecting distance increases.